A Model for Freight Transport crossing Storebælt - Sørensen, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 1997)
In this note a model for growth in total freight transport crossing Storebælt is put forward. First, a model forecasts redistribution of freight generated by reduced transportation costs caused by the Fixed Link. Redistributed freight originates from present internal traffic within Jylland/Fyn or Sjælland/Lolland-Falster that will cross Storebælt in the future after establishment of the Fixed Link. This is the gravity model. Second, the results from the gravity model is compared with the existing literature. In Section 2, the gravity model is analysed. Here, the applied data set is discussed and the model is formulated and estimated. Moreover, the model is applied to forecast redistributed traffic in rela- tion to establishment of the Fixed Link crossing Storebælt. In Section 3, the estimated elasticities of freight volumes with respect to the production value are discussed and compared to estimates available from existing literature. Section 4 concludes.